2013
DOI: 10.1109/tbme.2012.2225061
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Heart Rate Regulation in Cycle-Ergometer Exercises

Abstract: The heart rate can be effectively used as a measure of the exercise intensity during long duration cycle-ergometer exercises: precisely controlling the heart rate (HR) becomes crucial especially for athletes or patients with cardiovascular/obesity problems. The aim of this letter is to experimentally show how the nonlocal and nonswitching nonlinear control that has been recently proposed in the literature for the HR regulation in treadmill exercises can be effectively applied to cycle-ergometer exercises at co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 16 publications
0
21
0
Order By: Relevance
“…It can readily be shown that the nonlinear structure NL (Figure 1(b)) is identical to a linear PI compensator augmented with the static square-root compensation function (see Figure 1(c)), as proposed in the original references for this approach (Paradiso et al, 2013;Scalzi et al, 2012). To see this, consider the transfer function C PI from e to x in Figure 1…”
Section: Linear and Nonlinear Control Structuresmentioning
confidence: 98%
See 1 more Smart Citation
“…It can readily be shown that the nonlinear structure NL (Figure 1(b)) is identical to a linear PI compensator augmented with the static square-root compensation function (see Figure 1(c)), as proposed in the original references for this approach (Paradiso et al, 2013;Scalzi et al, 2012). To see this, consider the transfer function C PI from e to x in Figure 1…”
Section: Linear and Nonlinear Control Structuresmentioning
confidence: 98%
“…An alternative control approach based on the v 2 -nonlinear model from Cheng et al (2008) was developed and applied to both treadmill and cycle-ergometer exercise: see Scalzi, Tomei, and Verrelli (2012) and Paradiso, Pietrosanti, Scalzi, Tomei, and Verrelli (2013), respectively. This method countered the plant nonlinearity using the inverse nonlinearity, that is, the square-root function √ .…”
Section: Introductionmentioning
confidence: 99%
“…Heart rate (HR) can be used as an index to monitor the exercise intensity [18]. This fact makes it simpler to develop a control system to steer the human HR to a predetermined and individual exercise prescription, represented as a target HR profile, instead of directly employing the exercise intensity in kJoules or Watts and exercise rate (ER) as control parameters.…”
Section: Introductionmentioning
confidence: 99%
“…with a robust control algorithm in [26] and its modifications in [23]. Although the aforementioned papers constitute relevant solutions to general light control problems, when tracking of desired luminous color and intensity reference signals is repeatedly considered in the presence of completely uncertain dynamics-with the aim of reproducing a lighting profile similar to the one corresponding to a day cycle (in real world or even in virtual set scenarios) or, more interestingly, with the aim of benefiting from chromotherapy repetitive lighting profiles-possibly complex periodic output reference signals (with known period) naturally arise and repetitive learning control techniques 2 can be successfully used (see [8], [19] for recent theoretical results and [6], [7], [20], [21] for recent significant applications). In contrast to general nonlearning ones, repetitive learning controls are not model-based and actually use, in a repetitive uncertain scenario, the richness of information which error signals possess from previous executions [2] and [9]: while classical robust controllers can only theoretically achieve, through a proper choice of the control gains, exponential convergence of the output regulation or tracking error into residual sets whose size can be made arbitrarily small, repetitive learning controls are additionally able to guarantee asymptotic convergence to zero of the output regulation or tracking error in the presence of uncertainties.…”
Section: Introductionmentioning
confidence: 99%